1996
DOI: 10.3109/15563659609013809
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Hydroxocobalamin in Smoke Inhalation Victims

Abstract: The apparent volume of distribution suggests a predominantly extracellular partitioning of the antidote, even in the presence of cyanide, an important factor in terms of its antidotal effect. Hydroxocobalamin's elimination half-life in these cyanide-exposed patients far exceeds those found in previous studies of dogs and minimally-exposed humans. If confirmed, this half-life suggests that a single dose of hydroxocobalamin, sufficiently large enough to bind the cyanide present, should be adequate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 13 publications
0
24
0
2
Order By: Relevance
“…The mean half-life of free and total cob(III)alamins is approximately 26–30 hours after parenteral administration (Houeto et al 1996). A kinetic study in cblC disease patients showed that plasma B 12 levels peaked between 0.5 and 2 hours after administration and fell at a rate of approximately 12 mg/l/hr; the decrease in B 12 levels corresponded with an increase in metabolite levels (Van Hove et al 2002).…”
Section: Managementmentioning
confidence: 99%
“…The mean half-life of free and total cob(III)alamins is approximately 26–30 hours after parenteral administration (Houeto et al 1996). A kinetic study in cblC disease patients showed that plasma B 12 levels peaked between 0.5 and 2 hours after administration and fell at a rate of approximately 12 mg/l/hr; the decrease in B 12 levels corresponded with an increase in metabolite levels (Van Hove et al 2002).…”
Section: Managementmentioning
confidence: 99%
“…Cobalamins (e.g., OH-Cbl) have been used to treat humans with vitamin B 12 deficiency and cyanide poisoning successfully with no or few toxicities [37, 38]. Small doses of OH-Cbl (e.g., 1 mg daily to monthly given orally, intravenously, or intramuscularly) are used to treat vitamin B 12 deficiency, while much larger doses (e.g., 5 to 15 gm intravenously) are used to treat cyanide poisoning [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…Small doses of OH-Cbl (e.g., 1 mg daily to monthly given orally, intravenously, or intramuscularly) are used to treat vitamin B 12 deficiency, while much larger doses (e.g., 5 to 15 gm intravenously) are used to treat cyanide poisoning [37, 38]. The gram doses used for cyanide poisoning produce transient, mild hypertension as a side effect.…”
Section: Discussionmentioning
confidence: 99%
“…We used the hydroxocobalamin apparent volume of distribution of 0.45 L/kg and the maximum therapeutic dose of 10 g in a prototypical 70 kg person to determine that the peak therapeutic serum level of hydroxocobalamin is 317.46 mg/L [(1kg / 0.45L) × (1/70kg) × 10g × (1000mg/1g)=317.46 mg/ L] (2,18). A stock AA00Aaasolution of hydroxocobalamin (Spectrum Chemical Corp., Gardena, CA, USA) at twenty times this peak therapeutic level (20X) was made by dissolving hydroxocobalamin in a 0.9 N NaCl solution (6340 mg/L).…”
Section: Methodsmentioning
confidence: 99%